2020
DOI: 10.18632/aging.103259
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram for the prediction of diabetic nephropathy risk among patients with type 2 diabetes mellitus based on a questionnaire and biochemical indicators: a retrospective study

Abstract: Purpose: Develop a diabetic nephropathy incidence risk nomogram in a Chinese population with type 2 diabetes mellitus. Results: Predictors included systolic blood pressure, diastolic blood pressure, fasting blood glucose, glycosylated hemoglobin A1c, total triglycerides, serum creatinine, blood urea nitrogen and body mass index. The model displayed medium predictive power with a C-index of 0.744 and an area under curve of 0.744. Internal verification of C-index reached 0.737. The decision curve analysis showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 77 publications
0
29
0
Order By: Relevance
“…Data from a community-based study conducted by the Jiangsu Center for Disease Control and Prevention in 2013 indicated that high levels of SCr are strongly related to increased DN incidence risk among T2DM individuals [ 23 ]. Similarly, another retrospective study has reported that BUN and SCr levels are positively correlated with DN risk in T2DM patients [ 10 ]. In this study, the results of the logistic regression analysis also support the finding that levels of BUN and SCr are strongly associated with a higher risk of DN in patients with T2DM.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Data from a community-based study conducted by the Jiangsu Center for Disease Control and Prevention in 2013 indicated that high levels of SCr are strongly related to increased DN incidence risk among T2DM individuals [ 23 ]. Similarly, another retrospective study has reported that BUN and SCr levels are positively correlated with DN risk in T2DM patients [ 10 ]. In this study, the results of the logistic regression analysis also support the finding that levels of BUN and SCr are strongly associated with a higher risk of DN in patients with T2DM.…”
Section: Discussionmentioning
confidence: 98%
“…Our study is the first to build a nomogram model that includes inflammation-related indicators, such as NLR and RDW, in predicting the incidence risk of DN among T2DM patients. Hu et al [ 10 ] constructed a nomogram model to predict DN incidence risk, and the C-index of their nomogram was 0.744. Similarly, Jiang et al [ 35 ] established a prognostic nomogram to estimate renal prognosis in DN patients, and the C-index of the model was 0.79.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic nephropathy (DN) is characterized by albuminuria (>300 mg/day) and a reduced Glomerular Filtration Rate (GFR) [ 1 ]; it is the leading cause of the End-Stage Renal Disease (ESRD) worldwide. The incidence of DN in patients with Type 2 Diabetes Mellitus (T2DM) is 20–40% [ 2 ]. Thickening of the glomerular basement membrane, glomerulosclerosis, and expansion of the mesangial cells lead to kidney fibrosis in DN, however, the exact mechanisms implicated in the pathogenesis of DN are complex [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The least absolute shrinkage and selection operator (LASSO) method is suitable for the reduction of high-dimensional data for selecting risk factors with the best predictive features from patients undergoing spinal internal fixation surgery. The features with nonzero coefficients in the LASSO regression model were selected [ 16 , 17 ]. Then, based on the selected features of the model, a prediction model was constructed using multivariate logistic regression analysis.…”
Section: Methodsmentioning
confidence: 99%